Jules et Jim - Roché, Henri-Pierre 1879-1959; Delerue, Georges 1925-1992 (Tartan Video, 2002)
Twee mannen houden vóór, tijdens en na de Eerste Wereldoorlog van dezelfde vrouw die geen keus kan maken tussen hen.
Orig.: F 1962
Enth. Introduction to the film ; Jeanne Moreau audio commentary ; archival documentary material: François Truffaut talks about the book "Jules et Jim" (1966) ; Truffaut talks about his film and discusses a few scenes (1965)
Keywords: Film